The Encapsulation Effect on Viability of Mesenchymal Stem Cells: Pengaruh Enkapsulasi Terhadap Viabilitas Sel Punca Mesenkimal - Siburian, Marsudi; Sismindari; Rilianawati (Universitas Tadulako, 2021)
Stem cells are potentially used as a regenerative therapy agent. Cell encapsulation is one of the developed methods to utilize Mesenchymal Stem Cells (MSCs) for therapy. This research aimed to study the effect of encapsulation using alginate-CaCl2 towards the viability of hAdMSCs during in vitro culture. Encapsulation of hAdMSCs with alginate-CaCl2 was done using the extrusion method. The viability of hAdMSCs was analyzed with Live/Dead Assay and MTT assay. The results indicated that cultured hAdMSCs within alginate remain alive for 7 days culture period. However, the viability was lower than the reference culture. The absorbances from MTT assay of encapsulated MSCs were lower than the conventional hAdMSCs culture. This result indicated lower metabolic activity of hAdMSCs when cultured in alginate beads.